2019
DOI: 10.1161/circep.119.007311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Contact Force Monitoring and Unipolar Signal Modification as a Guide for Catheter Ablation of Atrial Fibrillation

Abstract: Background: Both contact force monitoring (CFM) and unipolar signal modification (USM) are guides for ablation, which improve the efficacy of pulmonary vein isolation of atrial fibrillation. We sought to compare the outcomes of atrial fibrillation ablation guided by CFM or USM. Methods: A total of 136 patients with paroxysmal atrial fibrillation underwent a circumferential pulmonary vein isolation using CF sensing ablation catheters and were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…USM is a qualitative indicator and indicates the real‐time evaluation of the transmural lesion creation while performing the PVI. It has been reported that the USM is a useful guide for the endpoint of each RF application while performing the PVI 5‐7,19 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…USM is a qualitative indicator and indicates the real‐time evaluation of the transmural lesion creation while performing the PVI. It has been reported that the USM is a useful guide for the endpoint of each RF application while performing the PVI 5‐7,19 …”
Section: Discussionmentioning
confidence: 99%
“…Every single RF delivery was performed with a 10 to 20 g contact force (CF) and was continued for at least 5 seconds (5‐10 seconds) after the unipolar atrial electrogram that was recorded by the ablation catheter, which always demonstrated a positive‐negative morphology before the ablation, had become completely positive (USM; Figure 1). 6 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations